Preparation and physicochemical characterization of Eudragit® RL100 Nanosuspension with potential for Ocular Delivery of Sulfacetamide - Bivash Mandal; Kenneth S Alexander; Alan T Riga (Frontiers Media S.A., 2010)
Purpose: Polymeric nanosuspension was prepared from an inert polymer resin (Eudragit® RL100) with the aim of improving the availability of sulfacetamide at the intraocular level to combat bacterial infections. Methods: Nanosuspensions were prepared by the solvent displacement method using acetone and Pluronic® F108 solution. Drug to polymer ratio was selected as formulation variable. Characterization of the nanosupension was performed by measuring particle size, zeta potential, Fourier Transform infrared spectra (FTIR), Differential Scanning Calorimetry (DSC), Powder X-Ray Diffraction (PXRD), drug entrapment efficiency and in vitro release. In addition, freeze drying, redispersibility and short term stability study at room temperature and at 40C were performed. Results: Spherical, uniform particles (size below 500 nm) with positive zeta potential were obtained. No significant chemical interactions between drug and polymer were observed in the solid state characterization of the freeze dried nanosuspension (FDN). Drug entrapment efficiency of the selected batch was increased by changing the pH of the external phase and addition of polymethyl methacrylate in the formulation. The prepared nanosuspension exhibited good stability after storage at room temperature and at 40C. Sucrose and Mannitol were used as cryoprotectants and exhibited good water redispersibility of the FDN. Conclusion: The results indicate that the formulation of sulfacetamide in Eudragit® RL100 nanosuspension could be utilized as potential delivery system for treating ocular bacterial infections.